Personality Factors and Job Satisfaction: Evaluating the Mediatory Role of Emotional Intelligence - Aida Mehrad (JETL (Journal of Education, Teaching and Learning), 2020)
According to the importance of academic staff job satisfaction at university and evaluating effective factors on satisfaction, the present study is to clarify the relationship between personality factors and job satisfaction by the mediatory role of emotional intelligence. The study involved 440 academic staff selected by multi-stage sampling from public research universities in Klang Valley, Malaysia. This study applied a cross-sectional design. Big Five Inventory (BFI), Emotional Intelligence Test (SSEIT), and Job Descriptive Index (JDI) have been used to measured variables of the study. Additionally, the Pearson correlation coefficient, multiple linear regression analysis, and mediation analysis (Sobel test) are used for data analysis. The findings released a positive correlation between emotion perception, utilization of emotion, managing own emotions, managing others’ emotions, conscientiousness, agreeableness, and openness with job satisfaction. Conversely, there is a negative correlation between neuroticism and job satisfaction, whereas no correlation is observed between extraversion and job satisfaction. Personality factors likewise showed a significant relationship with almost all emotional intelligence factors except the utilization of emotion and neuroticism. The utilization of emotion and neuroticism predicted the level of job satisfaction, and only utilization of emotion significantly mediated the relationships between agreeableness, conscientiousness, and openness with job satisfaction. In fact, the agreeableness, conscientiousness, and openness academic staff have a better ability to apply emotion to obtain job satisfaction than other staff. In short, the study sheds new light in the context of psychology, particularly in the job satisfaction context among academic staff at universities.